Every little thing - Young, Samantha (Hart's Boardwalk, 2017)
"The quiet town of Hartwell is the perfect place to get away from it all--and find what you never knew you needed... Bailey Hartwell has many reasons to feel content--her successful business, a close circle of friends, and her steady boyfriend...even if their romance feels staid after ten years without a serious commitment. The only challenge in her life comes in the form of sexy businessman Vaughn Tremaine. She thinks the ex-New Yorker acts superior and that he considers her a small-town nobody. But when Bailey's blindsided by a betrayal, she's shocked to discover Vaughn is actually a decent guy. Vaughn admires Bailey's free spirit, independence, and loyalty. As his passion for her has grown, his antagonism toward her has only worsened. Every little thing Bailey does seduces him. But when Vaughn's painful emotional past makes him walk away in fear he will hurt her, it opens an old wound in Bailey, and she uncharacteristically retreats. Once Vaughn begins to realize he's made the biggest mistake of his life, he has no choice but to fight like he's never fought before to convince Bailey that the love they've found together only comes around once in a lifetime.."--